SWOT Analysis of Batik Semarangan Competitiveness in The Disruption Era - Widiastuti, C. Tri; Santoso, Aprih (School of Business, IPB University (SB-IPB), 2022)
The unique feature of batik semarangan lies in the concept of colour according to the characteristic of Semarang. This study aims to analyze the strengths, weaknesses, opportunities, and threats of the batik semarangan competitiveness in the era of disruption. A research method is a qualitative approach using primary data, namely data obtained directly from the object under study through procedures and data collection techniques in the form of observation and structured interviews. The data analysis technique used is SWOT analysis (strengths, Weaknesses, Opportunities, and Threats). The validity test of the data includes the credibility test (internal validity) and the triangulation of sources. The results showed that (1) the strengths are the quality of batik, a very strategic location and support from the government to improve its business, and good relations with suppliers; (2) the weaknesses are the production process with simple technology, the lack of marketing for batik products, as well as elderly human resources with common knowledge; (3) the opportunity is that marketing is still extensive and can be done online; (4) the threat is the lack of regeneration of batik craftsmen, batik printing at lower prices. Business actors should increase their skills and creativity, improve product quality, and develop online marketing to increase competitiveness. This study also revealed several managerial implications, which are 1) policymakers must be present and participate in decision making, 2) ease of access to information, promotion and collaboration with batik business actors in big cities, 3) training and assistance to increase innovation and creativity, and 4) encouraging improved branding of batik semarangan. Keywords: disruption era, batik semarangan, competitiveness, SWOT